High SRD5A3 expression is correlated with promotion of proliferation and inhibition of apoptosis in B-cell non-Hodgkin lymphoma and suggests a poor prognosis - Shanshan Wei; Jie Sun; Jiahao Wen; Jianing Yu; Yixuan Xuan; Jingyu Huang; Jie Yang; Jianfeng Zhang (PLoS ONE, 2025)
Background Steroid 5α-reductase 3 (SRD5A3) is an important molecule involved in glycosylation and steroid hormone formation and is highly expressed in most tumors. However, The role of SRD5A3 in B-cell non-Hodgkin lymphoma (B-NHL) and its mechanism are unknown. Methods We used a multi-omics database to explore the expression and prognostic significance of SRD5A3 in various tumors, including B-NHL. We established SRD5A3 high- and low-expression B-NHL cell lines to test the effects of SRD5A3 on cell proliferation and apoptosis in vitro, and to analyze the signaling pathways associated with the effects of SRD5A3 on B-NHL. Results We found that SRD5A3 was highly expressed in most tumors, including B-NHL, and was more highly expressed in patients age ≥60 years, high levels of LDH, stage III-IV, non-GCB subtype, and extra-nodal invasion. Survival analysis showed that high SRD5A3 expression predicted poorer overall survival (OS). Further experiments showed that SRD5A3 high expression promoted B-NHL growth and attenuates apoptosis, conversely, SRD5A3 low expression inhibited B-NHL growth and promoted apoptosis. Western blot assay showed SRD5A3 promotes B-NHL cells growth by regulating the PI3K-AKT signaling pathway. Conclusions Our findings suggest that SRD5A3 exerts its oncogenic effects by regulating the PI3K-AKT pathway, may serve as a potential biomarker and therapeutic target for B-NHL, providing information for clinical decision-making.